Lack of evidence and standardization in care pathway documents for patients with ST-elevated myocardial infarction. (1st April 2016) - Aeyels, Daan; Van Vugt, Stijn; Sinnaeve, Peter R; Panella, Massimiliano; Van Zelm, Ruben; Sermeus, Walter; Vanhaecht, Kris
Abstract: Background: Clinical practice variation and the subsequent burden on health care quality has been documented for patients with ST-elevated myocardial infarction (STEMI). Reduction of clinical practice variation is possible by increasing guideline adherence. Care pathway documents can increase guideline adherence by implementing evidence-based key interventions and quality indicators in daily practice. Aims: This study aims to examine guideline adherence of care pathway documents for patients with STEMI. Methods: Lay-out, size and timeframe of submitted care pathways documents were analysed. Two independent reviewers used a checklist to systematically assess the guideline adherence of care pathway documents. The checklist comprised a set of key interventions and quality indicators extracted from evidence and international guidelines. The checklist distinguished the evidence level for each item and was validated by expert consensus. Results were verified by inviting participating hospitals to provide feedback. Results: Fifteen out of 25 invited hospitals submitted care pathway documents for STEMI. The care pathway documents differed in timeframe, lay-out and size. Analysis of the care pathway documents showed important variation in formalizing adherence to evidence: between hospitals, inclusion of 24 key interventions in care pathway documents varied from 13 to 97%. Inclusion of 11 essential quality indicators varied from 0 to 40%. Conclusion: Care pathway documents for patients with STEMI differ considerably in lay-out, timeframe and size. This study showed variation in, and suboptimal inclusion of, evidence-based key interventions and quality indicators in care pathway documents. The use of these care pathway documents might result in suboptimal quality of care for STEMI patients.